RESPONSABILIDADE CIVIL PELA GUARDA DO ANIMAL - WOITCHUNAS, LUCINÉIA FELIPIN; COLATTO, MARIANA SARETTO; ROSA, GIOVANA NATÁLIA; KERN, BIANCA; PASINATO, GISELI DA SILVA; SILVA, THIAGO DOS SANTOS DA (Salão do Conhecimento, 2025)
RESPONSABILIDADE CIVIL PELA GUARDA DO ANIMAL